AB0013 GENOMIC PROFILING OF INFLAMMATION-RELATED GENES IN NEURO-BEHçET SYNDROME: A PRELIMINARY ITALIAN STUDY. (June 2019) - Padula, Maria Carmela; Leccese, Pietro; Lascaro, Nancy; Carbone, Teresa; Limongi, Antonina Rita; Radice, Rosa Paola; Padula, Angela; D'angelo, Salvatore; Martelli, Giuseppe
Abstract : Background: Behçet Syndrome (BS) is a chronic vasculitis characterized by a wide spectrum of clinical manifestations, including the rare nervous system involvement, known as "Neuro-BS" (NBS) [1-3]. BS inflammatory features were studied in several genetics studies with focus on single nucleotide polymorphisms (SNPs) of genes involved in inflammation and immune response [4, 5]. A very few papers assessed the mutational state of NBS patients and this characterization was limited to a small number of SNPs [3]. Objectives: The aim of this study was to analyse the genetic background of a homogenous group of Italian NBS (parenchymal form) to genotype some SNPs of inflammation-related genes. Methods: NBS patients were extracted from our database and retrospectively studied. Molecular characterization was performed for a subset of 20 NBS patients and 42 sex-matched healthy controls (HC) via: a) bioinformatics consultation for SNPs selection and primer design; b) SNPs genotyping: DNA extraction, PCR amplification, direct sequencing; c) DNA variant analysis using similarity search tool and specific software. In a second phase of analysis, a group of 30 BS patients without neurological involvement (no-NBS) was also genotyped. The odds ratio (OR) was calculated to assess the strength of BS association for each genotype. Results: NBS patients subset was formed by 14 males and 6 females with mean age equal to 44.20 (±10.73) years. Six SNPs were considered eligible for molecular analysis and genotyped. Our results underlined the major role of ERAP1 rs17482078 (Table 1a ). rs17482078 GG genotype frequency was higher in controls (p-value<0.01), while GA genotype frequency was lower in the same group (p-value<0.05). rs17482078 AA genotype was absent in control group, while its frequency was equal to 10% for the patients (p-value<0.05). rs17482078 GA frequency was higher in NBS patients compared with no-NBS patients (p-value<0.01) (Table 1b ). No statistically significant differences were found for other SNPs of ERAP1 neither for IL-10 and STAT4 polymorphisms when NBS patients and controls were compared. Conclusion: Our results reported for the first time the genotype distribution of several susceptibility loci in a group of Italian NBS patients. The data suggest a possible association between ERAP1 rs17482078 and NBS. Larger analyses were required to verify our preliminary findings. References: [1] Saip S, et al. 2014. Handb Clin Neurol;121:1703-23; [2] Noel N, et al. 2014. Rev Med Interne;35(2):112-20. [3] Gheita TA, et al. 2015. Joint Bone Spine;82(3):213-5. [4] Gul A. 2015. Current Opinion in Rheumatology;26:56-63. [5] Takeuchi, et al. 2015. J Autoimmun. 2015;64:137-148. Acknowledgement: Many thanks to Professor Olivieri for his "heredity" Disclosure of Interests: Maria Carmela Padula: None declared, Pietro Leccese: None declared, Nancy Lascaro: None declared, Teresa Carbone: None declared, Antonina Rita Limongi: None declared, Rosa Paola Radice: None declared, Angela Padula Speakers bureau: Lilly Italia EMS, Salvatore D'Angelo: None declared, Giuseppe Martelli: None declared